2008
DOI: 10.1007/s11524-007-9250-y
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Child Health Inequities in Chandigarh Union Territory of India

Abstract: Health inequity is an emerging issue all over the world. Some populations living in specific geographic areas may have less access to basic health facilities. Therefore, a sample survey of households was carried out to study access of different population groups to reproductive and child health. Cluster sampling technique was used to select 30 clusters (18 urban, 9 slum, and 3 rural) from Chandigarh Union Territory in India. From each of these clusters, 40 households were selected randomly. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…A household survey from Chandigarh Union Territory comparing coverage of maternal health care showed that among the women studied, only 32% of the women living in urban-slum areas had an institutional delivery, compared to 93% of the non-slum urban women, and 79% of the women living in rural areas (14). The average maternal expenditure varies between geographical areas and between providers.…”
Section: Resultsmentioning
confidence: 99%
“…A household survey from Chandigarh Union Territory comparing coverage of maternal health care showed that among the women studied, only 32% of the women living in urban-slum areas had an institutional delivery, compared to 93% of the non-slum urban women, and 79% of the women living in rural areas (14). The average maternal expenditure varies between geographical areas and between providers.…”
Section: Resultsmentioning
confidence: 99%
“…24 Another study from India also indicated the poor utilization of maternal healthcare services in urban slums. 25 Even in some cases, women living in slum communities have less access and utilization of healthcare services than people of the rural areas [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…6 Recent research in Chandigarh that used primary data collected in 2006 showed that immunization status of children younger than 5 years was poorer in slum areas than in the rural and urban areas. 7 In contrast, a 2005---2006 National Family Health Survey (NFHS-3) report suggested that slum residents were not necessarily worse off than nonslum residents on several deprivation dimensions including poor health. 8 These studies have used prevalence rates of all illnesses, morbidity rates, incidence of hospitalization, and other health indicators as various proxies of health status.…”
mentioning
confidence: 99%